Preparation and Applications of Fluorinated Graphenes - Yasser Ahmad; Nicolas Batisse; Xianjue Chen; Marc Dubois (C, 2021)
The present review focuses on the numerous routes for the preparation of fluorinated graphene (FG) according to the starting materials. Two strategies are considered: (i) addition of fluorine atoms on graphenes of various nature and quality and (ii) exfoliation of graphite fluoride. Chemical bonding in fluorinated graphene, related properties and a selection of applications for lubrication, energy storage, and gas sensing will then be discussed.